STRATEGI PENGELOLAAN RUANG TERBUKA HIJAU DI KOTA SERANG BERBASIS TEKNOLOGI SISTEM INFORMASI GEOGRAFIS - Gina Maslahat; Muhlisin Muhlisin; Tauny Akbari (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
Population growth, increasing urban development and the high rate of conversion of green land into construction land pose a serious threat to the reduction of green open space (RTH) in Serang City. This research aims to determine the current condition of existing green open space, the need for green open space based on area, number population and oxygen needs, as well as strategies for optimizing green open space development in Serang City. The method used is quantitative descriptive with spatial analysis using remote sensing techniques and Geographic Information Systems (GIS). The results of the study show that Serang City's green open space in 2023 has met the city's minimum need for green open space of 30% of the total area, namely amounting to 59.64%. Serang City's need for green open space, if calculated based on its area, is 7,958.68 ha, based on its population, it is 1,440.72 ha, and based on its oxygen needs, it is 1,812.93 ha. The green open space management strategy that can be implemented in Serang City is a Growth Oriented Strategy which is oriented towards utilizing internal assets and external opportunities based on regional characteristics, active community participation, allocation of financial resources, establishing partnerships, developing infrastructure and a sustainable approach.